2018
DOI: 10.1016/j.ebiom.2018.08.040
|View full text |Cite
|
Sign up to set email alerts
|

COX-2–PGE2 Signaling Impairs Intestinal Epithelial Regeneration and Associates with TNF Inhibitor Responsiveness in Ulcerative Colitis

Abstract: BackgroundInhibition of tumor necrosis factor-α (TNF) signaling is beneficial in the management of ulcerative colitis (UC), but up to one-third of patients do not have a clinical response of relevance to TNF inhibitors during induction therapy (i.e. primary non-responders [PNRs]). Through production of prostaglandins (PGs) and thromboxanes, cyclooxygenase-2 (COX-2) affects inflammation and epithelial regeneration and may in this way be implicated in treatment resistance to TNF inhibitors.MethodsIn this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 42 publications
3
53
0
Order By: Relevance
“…enhancing Treg but limiting effector T cell responses 28,29 , but also suggest that targeting the PGE2 pathway may potentially be of beneficial in the control of intestinal inflammation. Our findings are further supported by a recent study demonstrating that PGE2 exacerbates TNF-induced inflammatory responses in human intestinal epithelial cells from patients with IBD who are resistant to TNF inhibitor therapy 46 . Moreover, recent studies including ourselves have suggested that lack of PGE2-EP4 signaling in T cells reduced both chemical-triggered acute and naïve T cell transfer-induced chronic intestinal inflammation, associated with reduction of inflammatory Th1 and/or Th17 cell responses 29,47,48 .…”
Section: Discussionsupporting
confidence: 88%
“…enhancing Treg but limiting effector T cell responses 28,29 , but also suggest that targeting the PGE2 pathway may potentially be of beneficial in the control of intestinal inflammation. Our findings are further supported by a recent study demonstrating that PGE2 exacerbates TNF-induced inflammatory responses in human intestinal epithelial cells from patients with IBD who are resistant to TNF inhibitor therapy 46 . Moreover, recent studies including ourselves have suggested that lack of PGE2-EP4 signaling in T cells reduced both chemical-triggered acute and naïve T cell transfer-induced chronic intestinal inflammation, associated with reduction of inflammatory Th1 and/or Th17 cell responses 29,47,48 .…”
Section: Discussionsupporting
confidence: 88%
“…Regardless of selective COX-2 inhibitors (COXIBS) manifested less GI damage [40], it is known that COX-2 has an essential role in enterocyte wound healing, through a mechanism related with NFKβ via and p38MAPK-dependent histone 3 phosphorylation, which is an important component of the intestinal wound-healing response [17], additionally PGE 2 participates in the differentiation of human goblet intestinal epithelial cells during homeostatic conditions [41] and PGI 2 in angiogenesis [10]. Bile salts seems also be related with intestinal damage cause by NSAIDs by forming super-toxic micelles [42,43], injuries that could be avoided by PC [44] evidencing the role of mucus barrier as protective factor of GI mucosa from lesions generated by NSAIDs.…”
Section: Figurementioning
confidence: 99%
“…TNF- α , PGE 2 , and IL-6 also play an important role in the inflammatory injury involved in UC ( Yamamoto et al, 2000 ; Gombošová et al, 2011 ; El Morsy et al, 2015 ; Sadar et al, 2016 ; El-Ashmawy et al, 2017 ; Gawrońska et al, 2017 ; Rafa et al, 2017 ; Li et al, 2018 ; Loynes et al, 2018 ). Moreover, GO analysis indicated that the proteins regulated by SNT in order to mediate its effects of UC play important roles in the pathogenesis of UC by regulating neutrophil degranulation, cell secretion, and other biological pathways.…”
Section: Discussionmentioning
confidence: 99%